THE BEHAVIOUR OF WOMAN CIGARETTE CONSUMEN (QUALITATIVE STUDY OF WOMAN ACTIVE SMOKER) - Dewi Rokhmah (UPT Penerbitan Universitas Jember, 2012)
Indonesia is one of developing country having high cigarette consumtion and production level. Although researchs showed smoking have health effect, the smoker is increas every year, especially woman smoker. Smoking is the simbols of modern, sexy, glamour, mature and independent women. They are potential target of tobacco industry. This study aims to analyze smoking behaviour (process become smoker, aged startedsmoking, reasons beeing smoker, level of cigarrette consumtion, the characteristic of cigarrette consumted, the place to smoke) on woman active smoker. It was a qualitative exploration involved informants aged 17-25 years, have been active smoker in last six mounts, with purposive sampling in Jember City. Data was collected by indepth interview and they’re analyzed by thematic content analysis. The result of this study showed that allinforman became smoker since children age from smoker family. They’re active smoker since at yunior or senior high school. The reason why they became active smoker because of sexy image, peer influence and stress decreasing effort . They prefer consumted white cigarette contented special taste (cappucino, chocolate, mint) because it content low tar and nicotine, 6 stem until 2 packs in a day.They smoke on their own house, cafe of night pub, and on their friend’s house. They never smoke on public area, because it acrossed the norms.